Exploring the Role of Knowledge on Adoptability of Islamic Banking and Financing Options for Micro, Small and Medium Enterprises: The Mediating Role of Trialability - Ali, Jazbeen; Kumar, Shalendra S.; Prasad, Vishwa H. (Journal of Ecohumanism, 2024)
Knowledge is the act of knowing something with familiarity gained through experience or education. Prior studies have discovered that knowledge has a significant relationship with the adoption of Islamic Banking and Financing Options (IBFOs) amongst Small and Micro Enterprises (SMEs). However, this study explores the role of knowledge on adoptability of Islamic Banking and Financing Options (IBFOs) for Micro, Small and Medium Enterprises (MSMEs), with the mediating role of trialability. While trialability has been suggested as an adoption factor, it has not been considered important in adoption studies and has thus received debates. A structured questionnaire survey consisting of a Likert scale from 1 to 5 was conducted with 300 MSME owners or managers. The findings revealed that trialability has a partial mediation between knowledge and adoptability of IBFOs. This implies that when IBFOs are offered on a trial basis, it will have an impact on the level of knowledge MSMEs will have about IBFOs with the adoptability of IBFOs. As a result, the banking and financing sector should consider offering IBFOs on a trial basis to enhance the knowledge of MSMEs and lead to its adoptability. This research contributes to literature by offering trialability as a mediating variable in the adoptability of IBFOs. The authors recommend testing trialability as a mediating variable in determining the adoptability of any other product or service or even testing it as a moderating variable.